TNF-α enhances the effect of TGF-β on Gli2 expression in the KG-1 leukemic cell line - LI, ZHE (D.A. Spandidos, 2014)
The Hedgehog (Hh) signaling pathway regulates a variety of tumor-related diseases, including leukemia. The present study aimed to determine whether there was an interaction between the Hh signaling pathway and transforming growth factor (TGF)-β in the KG-1 cell line. KG-1 cells were treated with TGF-β, tumor necrosis factor (TNF)-α and specific inhibitor of smad3 (SIS3). The expression level of Gli family zinc finger 2 (Gli2) was detected by quantitative polymerase chain reaction (qPCR) and western blot analyses. The results revealed that TGF-β significantly decreased the expression level of Gli2 in KG-1 cells, and that TNF-α and TGF-β together further reduced Gli2 expression in KG-1 cells. SIS3 inhibited the effect of TGF-β. These results suggest that Gli2 expression in KG-1 cells is suppressed by TGF-β in a Smad3-dependent manner, TNF-α can enhance the effect of TGF-β on Gli2 expression and that this occurs independently of Hh receptor signaling.